2021
DOI: 10.1186/s13063-021-05891-5
|View full text |Cite
|
Sign up to set email alerts
|

A survey of knowledge, perceptions and use of core outcome sets among clinical trialists

Abstract: Background Core outcome sets (COS) are standardised sets of outcomes, which represent the minimum outcomes that should be measured and reported in clinical trials. COS can enhance comparability across health trials by reducing heterogeneity of outcome measurement and reporting and potentially minimising selective outcome reporting. Examining what researchers involved in trials know and think about COS is essential to increase awareness and promote COS uptake. The aim of this study is therefore … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…20 However, education may not be the sole barrier, as some trialists prefer to measure their own outcomes instead of using a standardised set. 20 While trialists' preferences may explain the use of outcomes not listed in our COS, it is important to recognise that a COS is not intended to limit trialists from including their own outcomes. COMET encourages the use of additional outcomes while maintaining the COS as the minimum set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, education may not be the sole barrier, as some trialists prefer to measure their own outcomes instead of using a standardised set. 20 While trialists' preferences may explain the use of outcomes not listed in our COS, it is important to recognise that a COS is not intended to limit trialists from including their own outcomes. COMET encourages the use of additional outcomes while maintaining the COS as the minimum set.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors contributing to the lack of increased outcome measurement may include limited awareness of COS usage. A survey study by Belluci et al revealed that 35% of clinical trial researchers were not familiar with COSs, suggesting that education on COSs could be of benefit to trialists 20 . However, education may not be the sole barrier, as some trialists prefer to measure their own outcomes instead of using a standardised set 20 .…”
Section: Discussionmentioning
confidence: 99%
“…29 A lack of awareness of core outcome sets among researchers may be responsible. 30 The lack of validated PROM instruments is also a concern, with sometimes only poor-quality evidence existing to support an instrument’s validity. 31,32…”
Section: Patient-centred Outcomesmentioning
confidence: 99%
“…In 2019, a COS for aphasia (language impairment) after stroke was successfully developed [ 14 ]. There are challenges to implementation of COS [ 15 17 ] and uptake across different areas of health is variable. Some of the challenges related to the lack of appropriate measures, limited involvement of key stakeholders and a lack of awareness of the COS once developed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our study is to develop a consensus-based COS for dysarthria after stroke to agree ‘what’ outcomes of speech to measure and ‘how’ best to measure them. We intend to recruit relevant key stakeholders, establish what measures are appropriate and ensure we disseminate this COS in both clinical and research communities [ 15 ]. A COS for dysarthria would improve consistent and relevant outcome reporting for people with dysarthria in both clinical and research settings.…”
Section: Introductionmentioning
confidence: 99%